Estimating the reduction in HVAC load in multipurpose hall with the use of earth air tunnel heat exchanger (at Kathmandu University) - Gautam, Bibek; Bhattarai, Basanta; Bastakoti, Niranjan; Baral, Bivek (Journal of Innovations in Engineering Education, 2021)
Earth Air Tunnel (EAT) is a renewable form of Air Conditioning system applicable for both heating and cooling purposes with the utilization of Earth’s undisturbed temperature. The Multi-purpose hall located in Dhulikhel, Kavre has a warm and humid climate. The total cooling requirement for the hall is estimated to be 763.6 kW and the corresponding ventilation requirement is 6.03 m3/s (6.97kg/s at 32°C/55% RH). The Earth Air Tunnel is designed for pre-conditioning the ventilated air only. Considering the optimum length of 75m, the designed earth air tunnel has 10 units parallel tube of 75 m length, 400 mm diameter, and flow velocity of 4.8 m/s. The tunnel produces the cooling effect of 132 kW when the inlet and outlet temperatures are 32°C (55% RH) and 19°C (100% RH) respectively. Cooling during humid climate the output air has higher chances to be saturated and even condenses in the tube underground. Dehumidifying the air before entering the EAT can solve this problem and thus enhance the cooling effect during the humid season to some extent. With the assumed 1000 hours per year of operation, the estimated payback time at the rate of 4% per annum (assumed subsidized case) will be 15 years. Earth Air Tunnel must be given greater care for the hot and humid zone because the cost of Earth Air Tunnel will be very high in comparison to the heat pump and also the tunnel does not guarantee to give the intended performance throughout the year which does not seem to make the project feasible for the University hall.